Vitaliy Ivanovich Starostenko (On the seventy five-year-old Jubilee) (Геологічний журнал, 2010)
In April this year Vitaliy I. Starostenko, the famous Ukrainian scientist geophysicist in the field of theory of potential fields interpretation, automatized processing and interpretation of gravimetric and magnetometric data systems creation, theories and methodology, solving of inconsistently stated problems of geophysics, the problems of density models of the Earth's crust and upper mantle formation, celebrated the 75th anniversary.